Kinetics of B cell response during Yersinia enterocolitica infection in resistant and susceptible strains of mice - Cangiani, Eloisa Elena; Guiraldi, Fabricio Rodrigues; Sormus de Castro Pinto, Silvia Elena; Machado de Medeiros, Beatriz Maria (Taylor & Francis Inc, 2007)
In this study we analyze the B-cell response in murine yersiniosis. To this end, we determined whether polyclonal activation of B-lymphocytes occurs during infection of susceptible (BALB/c) and resistant (C57BL/6) mice with Y. enterocolitica 0:8 and compared the immunoglobulin (Ig) isotypes produced in response to the infection by the two strains. The number of splenic cells secreting nonspecific and specific immunoglobulins was determined by ELISPOT. The presence of anti-Yersinia antibodies in serum was detected by ELISA. In both strains, the number of specific Ig-secreting cells was relatively low. Polyclonal B-cell activation was observed in both strains of mice, and the greatest activation was observed in the BALB/c mice, mainly for lgG(1)- and IgG(3)- secreting cells. The C57BL/6 mice showed a predominance of IgG(2a)-secreting cells. The peak production of anti-Yersinia IgG antibodies in the sera of BALB/c mice was seen on the 28th day after infection. The greatest increase in IgM occurred on the 14th day. A progressive increase of specific IgG antibodies was observed in C57BL/6 mice up to the 28th day after infection while IgM increased on the 21st day after infection. The production of specific IgA antibodies was not detected in either BALB/c or C57BL/6 mice. We conclude that polyclonal. activation of B lymphocytes occurs in both the Yersinia resistant and Yersinia-susceptible mice and that the more intense activation of B lymphocytes observed in the susceptible BALB/c mice does not enhance their resistance to Y. enterocolitica infection.
Keywords: Yersinia enterocolitica; polyclonal B cell activation; specific antibodies